Chirp Interference Mitigation in GNSS Systems Using Chirp Parameter Estimation and Pulse Blanking - Nabil Jardak (IEEE Access)
Chirp interference is a major source of disturbance in Global Navigation Satellite System (GNSS) signal processing. Whether the chirp interference signal appears continuous or pulsed to a GNSS receiver depends on its bandwidth relative to the receiver bandwidth. This research proposes a method that reduces chirp interference in GNSS receivers for both continuous and pulsed chirp signals. It combines chirp estimation and suppression with pulse blanking. Simulation results indicate that L1C/A signal acquisition remains successful with up to 62 dB of jammer-to-noise ratio (J/No) for continuous chirp, and 30.5 dB for pulsed chirp. In terms of tracking performance, L1C/A GPS signals can be successfully tracked with J/No of up to 71 dB for continuous chirp and 55 dB for pulsed chirp. The technique was then subjected to a real-life GPS L1C/A signal summed with the strong signal of a commercial civil chirp jammer (J/No =34.2 dB). It has shown successful acquisition and tracking of all visible satellites with a C/No degradation less than 1 dB and a positioning error of a few meters, which confirmed the effectiveness of the technique. In addition to its attractive performance, the low complexity of the technique makes it practical for real-time implementation.